Using Different Forms of Assessment to Assess Young Language Learners - Rifa Andhini (UICELL, 2019)
Using different forms of assessment is beneficial. The practice will increase the reliability of the assessment itself and enable teachers to obtain deeper and richer information regarding students’ abilities. Even though it might present numerous challenges, applying the principle in assessment for young language learners can be advantageous as well. Thus, literature review was done so that rich information regarding the practice of using multiple sources in assessment, especially the ones intended for young language learners, can be presented in this paper. Based on the findings, it can be concluded that assessment for young language learners should not focus solely on tracking the learners’ progress. Instead, it should also aim to get the learners involved in the process and maintain their motivation in order to create strong “pillars” for their language learning journeys. Hence, adding forms of assessment that can cover those areas will increase the quality of the assessment. Self-assessment and portfolio are forms of assessment that can be used to reach the goals. These insights will be beneficial for teachers of young language learners who wish to achieve maximum results not only in terms of assessment, but also in the learning and teaching process as a whole. Keywords: assessment, language learners, young learners